The importance of protected areas for conservation of bare-faced curassow (Crax fasciolata spix, 1825) (Galliformes: Cracidae) in the Sao Paulo State, Brazil - Nascimento Gomes, Ana Paula; Fornitano, Larissa [UNESP]; Costa, Romulo Theodoro [UNESP]; Angeli, Thais [UNESP]; Rodrigues de Morais, Kimberly Danielle [UNESP]; Olifiers, Natalie; Bianchi, Rita de Cassia [UNESP] (Revista Biota Neotropica, 2018)
The Bare-faced Curassow Crax fasciolata (Cracidae:Cracinae) is a vulnerable species that was classified as critically endangered by the Sao Paulo State-Brazil, in 2008. Specialists recommended searches for areas where there may be a few remaining populations and protection of the last remaining semideciduous forest in the State. Protected areas were investigated in the Cerrado and semideciduous forest in Sao Paulo State by camera trapping to evaluate the presence of the Bare-faced Curassow. Eight protected areas in Cerrado biome were investigated, but the Bare-faced Curassows was recorded only at Fumas do Bom Jesus State Park (2,069 ha), Sao Paulo State despite the large sampling effort in larger protected areas such as the Santa Barbara Ecological Station (2,712 ha) and Jatai Ecological Station (9,074 ha); the largest protected area of Cerrado biome in Sao Paulo State. This record of C. fasciolata is important for the Conservation Action Plan for the Cracid family and shows the importance of monitoring biodiversity and conserving even relatively small remnants of native vegetation for the conservation of this species.
Keywords: Cerrado; camera trap; conservation; endangered birds